Generation of a C57BL/6 MYC‐Driven Mouse Model and Cell Line of Prostate Cancer. Issue 13 (26th May 2016) - Ellis, Leigh; Ku, ShengYu; Li, Qiuhui; Azabdaftari, Gissou; Seliski, Joseph; Olson, Brian; Netherby, Colleen S.; Tang, Dean G.; Abrams, Scott I.; Goodrich, David W.; Pili, Roberto
Abstract : INTRODUCTION: Transgenic mouse modeling is a favorable tool to reflect human prostate tumorigenesis and interactions between prostate cancer and the microenvironment. The use of GEMMs and derived cell lines represent powerful tools to study prostate cancer initiation and progression with an associated tumor microenvironment. Notably, such models provide the capacity for rapid preclinical therapy studies including immune therapies for prostate cancer treatment. METHODS: Backcrossing FVB Hi‐MYC mice with C57BL/6N mice, we established a Hi‐MYC transgenic mouse model on a C57BL/6 background (B6MYC). In addition, using a conditional reprogramming method, a novel C57BL/6 MYC driven prostate adenocarcinoma cell line was generated. RESULTS: Our results demonstrate that disease progression is significantly delayed in B6MYC when compared to their FVB counterparts. Current data also indicates infiltrating immune cells are present in pre‐cancer lesions, prostate intraepithelial neoplasia (PIN). Further, immunophenotyping of this immune infiltrate demonstrates the predominant population as myeloid‐derived suppressor cells (MDSC). Also, we successfully generated a B6MYC‐CaP cell line, and determined that this new PCa cell line express markers of luminal epithelial lineage. DISCUSSION: This novel model of PCa provides a new platform to understand the cross talk between MYC driven prostate cancer and the microenvironment. Importantly, these models will be an ideal tool to support the clinical development of immunotherapy as well as other novel therapeutic strategies for prostate cancer treatment. Prostate 76:1192–1202, 2016 . © 2016 Wiley Periodicals, Inc.